2020
DOI: 10.1038/s41598-020-70067-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a possible role of reactive oxygen species in magnetogenetics

Abstract: Recent reports have shown that intracellular, (super)paramagnetic ferritin nanoparticles can gate TRPV1, a non-selective cation channel, in a magnetic field. Here, we report the effects of differing field strength and frequency as well as chemical inhibitors on channel gating using a Ca 2+-sensitive promoter to express a secreted embryonic alkaline phosphatase (SEAP) reporter. Exposure of TRPV1ferritin-expressing HEK-293T cells at 30 °C to an alternating magnetic field of 501 kHz and 27.1 mT significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(93 citation statements)
references
References 61 publications
(122 reference statements)
3
82
0
Order By: Relevance
“…1C). The influence of the cellular iron import on ferritin iron load was corroborated by a recent study that reported that the ferritin iron core size depends on the presence of fetal bovine serum, ferric citrate and holotransferrin (Brier et al, 2020). Thus, the use of ferritin-based magnetogenetic tools in in vitro studies can be optimized by increasing the cellular iron import via holotransferrin supplementation or as reported recently, by a combination of holotransferrin and ferric citrate (Brier et al, 2020).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…1C). The influence of the cellular iron import on ferritin iron load was corroborated by a recent study that reported that the ferritin iron core size depends on the presence of fetal bovine serum, ferric citrate and holotransferrin (Brier et al, 2020). Thus, the use of ferritin-based magnetogenetic tools in in vitro studies can be optimized by increasing the cellular iron import via holotransferrin supplementation or as reported recently, by a combination of holotransferrin and ferric citrate (Brier et al, 2020).…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that RF fields at high kHz frequencies activate a ferritin-tagged TRPV1 (Brier et al, 2020; Stanley et al, 2015, 2016). Thus, we also estimated the E field amplitude for a 465 kHz RF stimulus of 31 μT which resulted in about 0.1 V/m (Figure S2A, B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations